2016
DOI: 10.1007/s40891-016-0044-8
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Interface Behaviour of Different Types of Granular Soil/Geosynthetics

Abstract: In this paper, influence of different types of soils and geosynthetics on soil/geosynthetics interface behaviouris investigated by direct shear and pullout tests. Three different types of cohesionless soils and three different types of geosynthetics materials are adopted for experimental investigation. A series of large direct shear tests and pullout tests were conducted to investigate the interface behaviour of soil/geosynthetics. The test equipment, soils, and geosynthetics properties are described. The infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Palmeira [1] presents test types that characterize, various conditions that can occur in some structures of reinforced soil. Some studies found in the literature, provides laboratory test results with the reinforcement layer positioned parallel to the failure plane induced for the shear box [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In other research the reinforcing layer is placed perpendicular or rotated to the failure plane [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Palmeira [1] presents test types that characterize, various conditions that can occur in some structures of reinforced soil. Some studies found in the literature, provides laboratory test results with the reinforcement layer positioned parallel to the failure plane induced for the shear box [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In other research the reinforcing layer is placed perpendicular or rotated to the failure plane [15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…While determining interface shear characteristics of soil-geotextile interface, geotextile was rigidly fixed to lower half of the direct shear box and in the other half soil was filled at desired compaction state. Geotextile was wrapped to a wooden box which fits perfectly into the modified direct shear [7,8]. Limit equilibrium method (LEM) and finite element method (FEM) are commonly adopted in evaluating stability of earthen structures [32].…”
Section: Methodsmentioning
confidence: 99%
“…Frictional and interface frictional characteristics are the important parameters governing the stability of sloped MLCS [5][6][7][8]. Moreover, it is presumed that interface layers (the plane between two different types of materials) are the weakest planes more prone to slip or failure due to the lack of proper interaction [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…where E c (%) is the effectiveness of strengthening with geosynthetic due to cohesion, E ϕ (%) is the effectiveness of strengthening with geosynthetic due to friction resistance, c a (kPa) is the adhesion between the soil and geosynthetic, c (kPa) is the soil cohesion, δ ( • ) is the angle of interfacial friction, and ϕ ( • ) is the angle of internal friction of the soil. The comparison of test results of soil shear strength parameters and friction parameters on the interface between soil and geosynthetic [4,6,[52][53][54] indicates that the values of the parameters E ϕ and E c are within a wide range (from 0.41 to 1.15 and from 0.45 to 1.41, respectively), but they are generally smaller than the value of 1.0. However, it should be noted that the usefulness of the E c parameter seems disputable (questionable) in the case when tested soil is non cohesive.…”
Section: Introductionmentioning
confidence: 98%